Lanskap Demonstrasi Jakarta: Komunikasi Politik Warga Kota dalam Ruang Publik - Muhamad Agung Dharmajaya; Aminah Swarnawati; M. Elfan Kaukab (Department of Political Science - Universitas Sains Al-Qur’an, 2026)
Demonstrations are an integral part of democracy in Jakarta, the largest city and capital of Indonesia. Throughout 2020, Pola Metro Jaya recorded 993 demonstrations, which reflects the high level of community participation in voicing important issues. This research maps the themes of demonstrations in Jakarta in the context of more integrative city development, using content analysis of online news headlines from 2014-2024. Using a constituency thematic framework with 12 frames, the results showed that five frames (ethnicity, age, religion, gender, and family) were not found in the demonstrations analyzed. Territorial and citizen frames dominate, followed by ideological, disadvantaged, functional, material and environmental frames. These findings suggest that territorial and public interest issues are more likely to trigger demonstrations in Jakarta, reflecting community sensitivity to land use and space requirements. Demonstrations are often related to broad public issues, emphasizing the importance of spatial justice and sustainable development.